2022
DOI: 10.3389/fbioe.2022.837619
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Loads: Modulation of IL-1 Induced Inflammatory Responses of Meniscal Cells in Two Models of Dynamic Physiologic Loading

Abstract: Meniscus injuries are highly prevalent, and both meniscus injury and subsequent surgery are linked to the development of post-traumatic osteoarthritis (PTOA). Although the pathogenesis of PTOA remains poorly understood, the inflammatory cytokine IL-1 is elevated in synovial fluid following acute knee injuries and causes degradation of meniscus tissue and inhibits meniscus repair. Dynamic mechanical compression of meniscus tissue improves integrative meniscus repair in the presence of IL-1 and dynamic tensile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 87 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…Cytokine treatment on nonhuman cartilage explants have been demonstrated to have an effect of increased release of ECM‐proteins and proteins involved in catabolic response of cartilage degradation into the explant culture media when compared to controls 48 . Combined mechanical loading and cytokine treatment on porcine and bovine meniscus was recently reported by McNulty et al in which two mechanical treatments were used; cell stretching and dynamic loading, using transcriptomics 49 . The inflammatory response was highly modulated by mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokine treatment on nonhuman cartilage explants have been demonstrated to have an effect of increased release of ECM‐proteins and proteins involved in catabolic response of cartilage degradation into the explant culture media when compared to controls 48 . Combined mechanical loading and cytokine treatment on porcine and bovine meniscus was recently reported by McNulty et al in which two mechanical treatments were used; cell stretching and dynamic loading, using transcriptomics 49 . The inflammatory response was highly modulated by mechanical loading.…”
Section: Discussionmentioning
confidence: 99%
“…48 Combined mechanical loading and cytokine treatment on porcine and bovine meniscus was recently reported by McNulty et al in which two mechanical treatments were used; cell stretching and dynamic loading, using transcriptomics. 49 The inflammatory response was highly modulated by mechanical loading. In our study of menisci, we find release of ECM-and catabolic proteins, although the specific proteins released are to a large degree different than previous studies using a cartilage model.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 participates in the onset of OA as it leads to the expression of nitric oxide, matrix metalloproteinases that degrade the ECM of the meniscus tissue, and inhibits the proper mechanical properties as well as the repair of the fibrocartilage [113]. Interestingly, a recent study performed on meniscal explants of the inner and outer regions as well as isolated meniscus cells submitted to physiological mechanical loading (compression and cyclic tensile stretch), revealed that mechanical stimulation can strongly modulate the transcriptomic profile that is activated by IL-1, and can decrease the expression of genes involved in inflammatory signaling and OA development [114]. These new results open the hope of increasing the capacity of the meniscus for repair by targeting the meniscus mechanotransduction.…”
Section: Optimization Of the Mechanical Propertiesmentioning
confidence: 99%